Nanomaterials in Daily Life Compounds, Synthesis, Processing and Commercialization - Abdullaeva, Zhypargul; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book describes nanomaterials used and existing in the environment, food industry and packaging, health care products and cosmetics, housekeeping, nanomaterials for cleaning purposes, architectural building products, medicine, clothing and textile, smart electronics and sensors. Each chapter provides basic knowledge on synthesis of nanomaterials by biological approaches. Fundamental terms are defined, followed by explanatons, examples, visual photographs, schemes and illustrations. .
Nanomaterials in the Environment -- Nanomaterials in Food Industry and Packaging -- Nanomaterials in Healthcare and Cosmetics -- Nanomaterials in Medicine -- Nanomaterials for Building and Protection -- Nanomaterials for Clothing and Textile Products -- Smart Electronics and Sensors.
Keywords: Nanotechnology; Nanoscience; Environmental chemistry; Food science; Pharmacology; Electrical engineering; Nanotechnology; Nanophysics; Environmental Chemistry; Food Science; Pharmacology; Electrical and Electronic Engineering